Evolution and Current Trends in STEM Education: A Retrospective and Bibliometric Analysis - Elizaveta Vitalievna Sokolova; Victor Andreevich Blaginin; Alexandra Yaroslavovna Shatrova (Sagamedia Teknologi Nusantara, 2025)
This study explores the evolution of STEM education, tracing its historical origins through contemporary trends and challenges. The research aims to address the need for a comprehensive understanding of current trends and directions in STEM education to align educational practices with societal demands and the evolving 21st-century labor market. The study employed a two-stage methodology: 1) a retrospective analysis of scientific literature to identify key concepts and historical milestones shaping STEM education, and 2) a bibliometric analysis of publications from the past three years (2021–2024) indexed in the OpenAlex database. The bibliometric analysis revealed emerging research clusters and themes, emphasizing trends such as interdisciplinary and transdisciplinary learning and the integration of advanced pedagogical technologies, including digital tools and AI-driven platforms. Key findings highlight the critical role of interdisciplinary approaches in fostering critical thinking, bridging disciplinary divides, and preparing students to solve complex real-world problems. The study identifies promising trajectories for STEM education’s future development, including enhanced integration of STEM disciplines, adoption of innovative pedagogical strategies (e.g., project-based learning), and collaborative frameworks involving educators, policymakers, and industry stakeholders. These insights provide a foundation for advancing STEM education in ways that respond to societal challenges and the dynamic needs of the global workforce.